2018
DOI: 10.2298/mpns1804131z
|View full text |Cite
|
Sign up to set email alerts
|

Meteoropathy and meteorosensitive persons

Abstract: Introduction. The authors are dealing with the questions often asked by their patients: how weather changes, oscillations in humidity, air pressure and other climate factors affect functioning of the human body. Meteorology and Biometeorology. Definitions of meteorology and biometeorology are given, describing some of the most important characteristics, such as the types of disorders and the reasons for their occurrence, frequency, gender and age factors, etc. with particular reference to disorders related to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(33 citation statements)
references
References 0 publications
0
5
0
1
Order By: Relevance
“…Although the biological mechanisms of meteoropathy are unknown, in a recent study, it was suggested that superior vestibular nucleus activity may affect meteoropathy regulation in mice and probably in humans [18]. Furthermore, the activities of the hypothalamus and amygdala nucleus are suggested as significant in meteoropathy development [19]. The authors suggested electromagnetic waves directly affect the hypothalamus.…”
Section: Introductionmentioning
confidence: 99%
“…Although the biological mechanisms of meteoropathy are unknown, in a recent study, it was suggested that superior vestibular nucleus activity may affect meteoropathy regulation in mice and probably in humans [18]. Furthermore, the activities of the hypothalamus and amygdala nucleus are suggested as significant in meteoropathy development [19]. The authors suggested electromagnetic waves directly affect the hypothalamus.…”
Section: Introductionmentioning
confidence: 99%
“…They should also stay in ventilated rooms and take hot and cold showers to help improve their circulation. Smoking and alcohol can increase body temperature and should be avoided [ 24 , 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, the potential side effects of commonly used drugs in meteoropathic patients, such as diuretics, angiotensin-converting enzyme inhibitors, angiotensin II receptor blockers, and psychoactive drugs, are still unknown [ 24 , 38 ]. Since vasodilatation is a side effect of diuretics but also occurs in thermoregulation, diuretics should be reduced in meteoropathic individuals to prevent extremely dangerous situations [ 38 , 39 ].…”
Section: Potential Therapeutic Agents For Meteoropathymentioning
confidence: 99%
See 1 more Smart Citation
“…Mintegy következtetésként elmondható, hogy az éghajlatváltozás, a környezetszennyezés és a világjárványok, köztük a jelenleg is zajló COVID-19 világjárvány negatív hatással lehetnek a mentális egészségre (Cianconi et al, 2020). Régóta ismert, hogy a légszennyezés és a meteorológiai változások pszichopatológiai jelenségeket, például meteoropátiát idézhetnek elő, amely kifejezés jelenleg az időjárási körülményekkel kapcsolatos bármely kóros dimenzió megjelölésére szolgál (Žikić-Rabi-Žikić, 2018). Továbbá, a környezeti szennyező anyagok, az éghajlatváltozás és a SARS-CoV-2 fertőzés összefüggésbe hozható a központi idegrendszerben (CNS) bekövetkező változásokkal, amelyek mentális és/vagy viselkedési elváltozásokhoz vezethetnek különböző (Marazziti et al, 2021).…”
Section: áBra: Co2 Kibocsátásának Lehetséges Alakulása Az Iea Illetve...unclassified